Antiretroviral treatment interruption and resumption within 16 weeks among HIV-positive adults in Jinan, China: a retrospective cohort study - Ma, Jing; Jin, Yan; Jiao, Kedi; Wang, Yao; Gao, Lijie; Li, Xinrui; Ma, Wei (Frontiers in Public Health, 2023)
Background Treatment interruption has been found to increase the risk of opportunistic infections and death among HIV-positive adults, posing a challenge to fully realizing antiretroviral therapy (ART). However, it has been observed that short-term interruption (<16 weeks) was not associated with significant increases in adverse clinical events. There remains a dearth of evidence concerning the interruption and resumption of ART after short-term discontinuation in China. Methods HIV-positive adults who initiated ART in Jinan between 2004 and 2020 were included in this study. We defined ART interruption as more than 30 consecutive days off ART and used Cox regression to identify predictors of interruption. ART resumption was defined as a return to ART care within 16 weeks following discontinuation, and logistic regression was used to identify barriers. Results A total of 2,506 participants were eligible. Most of them were male [2,382 (95%)] and homosexual [2,109 (84%)], with a median age of 31 (IQR: 26–40) years old. Of all participants, 312 (12.5%) experienced a treatment interruption, and the incidence rate of interruption was 3.2 (95% CI: 2.8–3.6) per 100 person-years. A higher risk of discontinuation was observed among unemployed individuals [adjusted hazard ratio (aHR): 1.45, 95% CI: 1.14–1.85], with a lower education level (aHR: 1.39, 95% CI: 1.06–1.82), those with delayed ART initiation (aHR: 1.43, 95% CI: 1.10–1.85), receiving Alafenamide Fumarate Tablets at ART initiation (aHR: 5.19, 95% CI: 3.29–8.21). About half of the interrupters resumed ART within 16 weeks, and participants who delayed ART initiation, missed the last CD4 test before the interruption and received the “LPV/r+NRTIs” regimen before the interruption were more likely to discontinue treatment for the long term. Conclusion Antiretroviral treatment interruption remains relatively prevalent among HIV-positive adults in Jinan, China, and assessing socioeconomic status at treatment initiation will help address this issue. While almost half of the interrupters returned to care within 16 weeks, further focused measures are necessary to reduce long-term interruptions and maximize the resumption of care as soon as possible to avoid adverse clinical events.